Sibu Rural District Council (SRDC) at Wisma Sanyan / Kaylyn Bayat - Bayat, Kaylyn (Universiti Teknologi MARA, Sarawak, 2016)
Sibu Rural District Council (Majlis Daerah Luar Bandar Sibu) and also known as (MDLBS or SRDC) is a local authority which administers Sibu rural areas such as Sibu Jaya and Selangau District. Besides that, Sibu Rural District Council (SRDC) is under the purview of Sarawak Ministry of Local Government and Community Development. Furthermore, the establishment of this council is to provide basic amenities, public infrastructure, and professional services to the community under its jurisdiction. Besides that, Sibu Rural District Council (SRDC) was constituted on 1 January 1952 but its birth stretched way back to the 1940s. Moreover, the roots of Sibu Rural District Council (SRDC) can be dated back to 1940 where it was known as "Dayak Local Authority" which was under the chairmanship of Penghulu Imai. In additional, during that times most of their members were comprimising of the Iban local chiefs of Sibu. Thereafter it was placed under the administration of the British colonial officers embracing a new name of The Local Authority Sibu. In 1997 the Council embarked on achieving the Municipal status by 2010. Apart from that, in 1981 due to a delineation exercise, one of the areas under Sibu Rural District Council (SRDC) was incorporated under Sibu Municipal Council (SMC). Moreover, another area known as Igan region also was incorporated under Matu and Daro District Council in October 1991. Over the last 6 decades, Sibu Rural District Council (SRDC) has evolved from a small council into one of the leading district councils in Sarawak. In other words, today with strength of 76 staffs, it oversees the administration of 2 districts, namely the Sibu and Selangau District covering an area of nearly 6,000 sq. km. Its current population is close to 60,000 which comprised of the Ibans and other bumiputera living in the rural area with the Chinese living in towns and other settlements along the mighty Rejang River.